Limb ablation and regeneration in Harmonia axyridis: costs for regenerators, but benefits for their progeny. Issue 2 (23rd February 2018) - Abdelwahab, Ahmed H.; Michaud, J.P.; Bayoumy, Mohamed H.; Awadalla, Samir S.; El‐Gendy, Mohamed
Abstract: Previous work revealed that Harmonia axyridis Pallas (Coleoptera: Coccinellidae) in Beijing, China, were capable of regenerating a forelimb amputated in the fourth instar; 75% of surviving individuals fully regenerated the limb during pupation. In this study, we tested a population of H. axyridi s invasive in North America and found that virtually 100% of beetles surviving the operation successfully regenerated the limb. Ablated/regenerated beetles spent longer in pupation, and emerging females were smaller than controls. However, reproductive success was unaffected in all pairwise crosses of control/regenerated adults; there were no differences in pre‐oviposition period, the time required to produce 10 clutches, 10‐day fecundity, or the fertility of eggs, whereas ablated/regenerated parents paid a developmental cost, their progeny obtained benefits. Offspring of crosses that included a regenerated parent tended to have faster larval development than the control cross, although not all were significantly different from controls. However, when either or both parents were ablated and regenerated, their daughters were heavier than controls at emergence. Limb regeneration during pupation appears to activate a physiological cascade which increases the magnitude of beneficial parental effects normally conferred to progeny, possibly via pleiotropic effects. The invasive North American H. axyridis population appears to have higher regeneration capacity than the Chinese population tested previously, although how regeneration capacity might be associated with invasiveness remains unclear. Limb regeneration ability may be a side effect of selection on other traits that confer high fitness under either natural or sexual selection, as it seems unlikely to confer fitness benefits directly in this species. Abstract : Harmonia axyridis (Coleoptera: Coccinellidae) in China are capable of regenerating a forelimb during pupation. In this study, we tested a population invasive in North America and found that virtually all beetles surviving the operation regenerated the limb. Compared to controls, ablated/regenerated beetles spent longer in pupation, and emerging females were smaller, but their reproductive performance was similar. Offspring of crosses that included a regenerated parent had faster larval development and daughters were heavier at emergence.